The Effect of “Insufficient Milk Supply” Concept Intervention on Mother's Perception of Breast Milk Production - Mekar Dwi Anggraeni; Lutfatul Latifah; Ima Rismawati (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2016)
Background: World Health Organisation (WHO) recommends every mother to provide exclusive breastfeeding for their infants because of its benefits. However the exclusive breastfeeding rate in Indonesia was only 35%in 2013. One of the main factors affecting low exclusive breastfeeding rate was maternal perception of having low breastmilk supply. There were no previous studies examining the effect of